Transnational commercial law : text, cases and materials - Goode, Royston Miles; Kronke, Herbert; McKendrick, Ewan (Oxford University Press, 2015)
'Transnational Commercial Law' brings together all the necessary materials on this topic in a logical and accessible way. The authors provide students with an extensive discussion on the theoretical issues raised by the law.